The influence of community on Transient evoked otoacoustic emissions (TEOAEs) in Iraqi subjects with normal hearing. - Al-Namir, Munir S.; Al-Doori, Falah N.; Essa, Maha A. (Journal of the Faculty of Medicine Baghdad, 2010)
Background: The purpose of this study was to compare the parametric measurements of transient otoacoustic (TEOAEs) in normal hearing subjects between two clinical centers in Iraq and to examine the community effect on TEOAEs characteristics.Patients and Methods: Transient otoacoustic emission (TEOAEs) were obtained from eighty subjects (160 ears)-males and females aged (10-20 years), with Forty (40) subjects in Baghdad audiology center and forty subjects in Sulaimania audiology center (North of Iraq)[ Kurdistan-Iraq], in standard, non-linear “Fast Screen” mode. Hearing thresholds, tympanometric, and TEOAE-parameters were recorded between two clinical center groups.Results: The cross correlation (wave reproducibility) was constant between two groups. The mean Signal to noise ratio (SNRs) for all (160 ears) were well above 3 dB at frequencies 1K, 2K, 3K, 4K and 5 KHz. The Sulaimania –subjects group showed the lowest SNR in low frequency (1 KHz) and middle frequency (3 KHz) than the Baghdad-subjects group. No statistical difference was observed in other frequency bands, and in overall mean SNRs between two groups.Conclusions: The observed differences of SNRs at low and middle frequency bands are most likely related to differences in ear canal volume and/or to differences in cochlear mechanisms. The values obtained in the present study can be used as normative data for screening and diagnostic purposes in Iraqi subjects aged (10-20 years).